Flash 8 graphics, animation, and interactivity - Mohler, James L. (Thomson/Delmar Learning, 2006)
Through five releases of Macromedia's industry-standard Web graphics software program, James Mohler has become the indispensable resource for those looking to master the power of Flash. Flash:8 Graphics, Animation & Interactivity delivers Mohler's widely praised hands-on approach to learning for the newest version of Macromedia Flash. Exercises and examples in the book, and the on back-of-the book CD, combined with step-by-step explanations, provide the best of both worlds-not just telling you how flash works, but showing you as well. For those new to flash, there are plenty of exercises designed to quickly get users up to speed quickly.